Epithelioid Hemangioendothelioma in a Liver Transplant Recipient: A Case Report of an Extremely Rare Tumor - Gonçalves,Margarida (2024)
Abstract Epithelioid hemangioendothelioma is a very rare vascular neoplasm, which is often multifocal or metastatic at diagnosis. Most frequently arises in the liver, followed by the lung and bones. The authors present a case of a liver transplant recipient who developed a pattern of hepatic cholestasis associated with the appearance of a proliferative hepatic lesion with inﬁltrative growth. Histological examination and immunohistochemical study were compatible with the diagnosis of epithelioid hemangioendothelioma. Pulmonary micronodules were detected and lung metastases were hypothesized. Therefore, bronchoscopy was performed, which turned out to be normal, and cytology was negative for neoplastic cells. After a multidisciplinary discussion, liver retransplantation was decided. After 8 years of follow-up, the patient is clinically stable, with no graft dysfunction, no neoplastic recurrence, and dimensional stability of the pulmonary micronodules. Patients with organ transplant have higher risk of developing carcinoma compared to the general population. The development of cancer is a multifactorial process and little is known about the etiology of epithelioid hemangioendothelioma. No standard treatment strategy has been deﬁned yet, and the natural course of the disease is heterogenous and the individual prognosis unpredictable. Complete surgical resection is offered to patients with unifocal disease, and those with unresectable disease should be evaluated for orthotopic liver transplantation.